(untitled) (Journal of the College of Basic Education, 2023)
The religious leadership exercised an important activity in Iran’s religious and political life. Perhaps the Safavid era was considered a golden era in the history of the (religious institution), which extended to the Karjari era. During these two eras, the opposition stood at times and by peaceful coexistence at other times.